Hindu perspectives on evolution: Darwin, dharma, and design - Brown, C. Mackenzie (Routledge Hindu studies series, 2012)
Design and Darwin in the Hindu dharma traditions -- Creationism and evolutionism in the ancient and classical traditions -- Manifestation and apparent design in the Advaita Vedānta of Śaṅkara -- Theism and atomistic design in the Nyāya-Vaiśeṣika of Udayana -- Design discounted in the Viśiṣṭādvaita Vedānta of Rāmānuja -- Design and Darwin in the colonial period -- The Vedāntic deism of Rammohan Roy -- Design and the intuitive theism of Debendranath Tagore -- Design and the religious evolutionism of Keshab Chandra Sen -- The modern Vedic creationism of Dayananda Saraswati -- The modern Advaitic evolutionism of Swami Vivekananda -- The integrative evolutionism of Sri Aurobindo Ghose -- Design and Darwin in the post-colonial period -- Design and Darwin in the contemporary Hindu world -- Conclusion : what role for Brahmā?